Pollen morphology of some Veronica species (Plantaginaceae) from Turkey - Varlik, Kader; Armağan Meti̇n; Bülbül Ali̇ Savaş (Phytotaxa, 2022)
The aim of the present work is to provide an account on the morphological features of pollen of Veronica species in Turkey, as a contribution to future research. Pollen morphology of 20 species of the Veronica were investigated using Light Microscope (LM) and Scanning Electron Microscope (SEM). Different palyno-morphological features including; pollen ornamentation, colpus ornamentation, size of polar and equatorial diameter, P/E ratio, exine thickness, and size of colpus were observed. The study revealed that the pollen grains of the studied Veronica species were in all cases tricolpate, radially symmetrical and isopolar, oblate-spheroidal or prolate spheroidal. The surface pattern of the exine varied from striato-reticulate and striato-microreticulate to microechinate-perforate, which allows recognition of three homonymous types of pollen grains.